The Effect of Coating Patterns with Spinel-Based Investment on the Castability and Porosity of Titanium Cast into Three Phosphate-Bonded Investments - Pieralini, Anelise R. F. [UNESP]; Benjamin, Camila M. [UNESP]; Ribeiro, Ricardo Faria; Scaf, Gulnara [UNESP]; Adabo, Gelson Luis [UNESP] (Wiley-Blackwell, 2010)
Purpose: This study evaluated the effect of pattern coating with spinel-based investment Rematitan Ultra (RU) on the castability and internal porosity of commercially pure (CP) titanium invested into phosphate-bonded investments. The apparent porosity of the investment was also measured.Materials and Methods: Square patterns (15 x 15 x 0.3 mm(3)) were either coated with RU, or not and invested into the phosphate-bonded investments: Rematitan Plus (RP), Rema Exakt (RE), Castorit Super C (CA), and RU (control group). The castings were made in an Ar-arc vacuum-pressure machine. The castability area (mm(2)) was measured by an image-analysis system (n = 10). For internal porosity, the casting (12 x 12 x 2 mm(3)) was studied by the X-ray method, and the projected porous area percentage was measured by an image-analysis system (n = 10). The apparent porosity of the investment (n = 10) was measured in accordance with the ASTM C373-88 standard.Results: Analysis of variance (One-way ANOVA) of castability was significant, and the Tukey test indicated that RU had the highest mean but the investing technique with coating increased the castability for all phosphate-bonded investments. The analysis of the internal porosity of the cast by the nonparametric test demonstrated that the RP, RE, and CA with coating and RP without coating did not differ from the control group (RU), while the CA and RE casts without coating were more porous. The one-way ANOVA of apparent porosity of the investment was significant, and the Tukey test showed that the means of RU (36.10%) and CA (37.22%) were higher than those of RP (25.91%) and RE (26.02%).Conclusion: Pattern coating with spinel-based material prior to phosphate-bonded investments can influence the castability and the internal porosity of CP Ti.
Keywords: Titanium; dental casting investment; dental prosthesis; porosity; dental materials